(untitled) (JURNAL PROTEKSI KESEHATAN, 2020)
One of the goals of patient safety (IPSG) is third goal, which focuses on the safety of treatment, especially the high-alert medications. Medication errors are the third leading cause of death after heart disease and cancer. This incident can be detrimental to the patient and can endanger patient safety which can be done by health workers, especially in giving drugs to patients. For this reason, it is necessary to know how much the nurses knowledge about this matter. The study was a descriptive study with a sample of nurses in the inpatient rooms of two hospitals in Pekanbaru. The results shows that 55% and 48% of respondents have good knowledge of the third goal.